An Effective Analysis on Human Rights of Older People in India: A Critical Examination of the Violation of Human Rights in the Context of Aging Population in India (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Old age is an irreplaceable phase of life of an individual which a man can't discredit with the exception of troublesome passing. The adolescence and old age are regular dependent states of life where kids rely upon guardians and the other way around. The idea of atomic family influenced this standard cycle bringing about misbalance of the ordinary existence of elderly individuals by vanquishing thousand years of age routine with regards to India where guardians are dealt with as a devout type of God. These days, the guardians are getting to be noticeably oppressive for their kid at whatever point they lost their quality to work and acquire. Accessible lawful, social, moral and administrative standards are broke down in this article to discover the conceivable courses by which elderly individuals' human rights are encroached and they bound to endure torment and distress. The article also reflects the available laws, policies and guidelines for the protection of the rights of old age person in India.